RECONSTRUCTING THE STATUS OF CONSTITUTIONAL COURT RESEARCHERS: MEREKONSTRUKSI STATUS PENELITI MAHKAMAH KONSTITUSIONAL - Barus, Sonia Ivana; Saifulloh, Putra Perdana Ahmad; Amancik; Nikenuna, Syifa (Constitutional Law Society, 2026)
Researchers at state institutions were forced to leave their positions, including those at the Constitutional Court. Researchers then lose the opportunity to hold the title of research professor. These researchers were also given a new duty, which was to help courts and give Constitutional Justices substantial support. The predicate “assistance" in this rule, which receives no detailed explanation, leads to multiple interpretations and affects the productivity of assistants to expert constitutional judges. Based on this, it is interesting to discuss how the status quo regulates career paths and academic freedom of Constitutional Court researchers in personnel law and how the ideal concept of setting career paths and academic freedom for researchers at the Constitutional Court. This study uses a normative research method, in which its results implicitly suggest a return to the previous rules. The researcher also suggests that the positions of assistant judge and researcher be strictly separated and that opportunities be provided for researchers to hold the title of academic professor. Researchers think BRIN should merge research institutions with the same form and function.